Information technologies for the information agent - Magalhães, Paulo Sérgio Tenreiro (2007)
The information agent has requirements in the Information Technology (IT) age that are in everything comparable to those of one hundred years ago. But, despite being similar, they require new forms of implementation due to the evolution of the communication platforms and protocols and to the increase in the amount of information that has to be known, stored, transmitted, and interpreted. Although, in many situations, the information agent will make use of everyday equipment, he will always require levels of trust in the processes that are far beyond those of the everyday citizen. But this cannot imply to carry huge infrastructures that will reveal the agent’s intentions. In extreme situations the information agent is the soldier engaged in military activities in hostile environments. There, above all places, he requires light weight trustable equipment and protocols that can perform those tasks. This work, while making the parallel with the traditional methods, proposes a technological environment able to give answer to the requirements of information agents dealing with the need for a competitive intelligence advantage through the correct use of IT, namely biometrics, alternative authentication processes, Public Key Infrastructures and anti-fishing technologies.